Day 3 Wed, August 07, 2019 2019
DOI: 10.2118/198827-ms
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Properties of Terminalia Mantaly Exudate as Drilling Mud Additive

Abstract: Polymers are known for controlling fluid loss and modifying rheology in drilling muds through polymer chain entanglement and polymer-solvent interactions. Natural polymers have been used in the formulation of drilling muds, mainly due to their high molecular weight and eco-friendliness but they have limitations in controlling fluid loss, modifying viscosity or forming good gel strength in saline and thermal environments. This study reports laboratory evaluation of Terminalia mantaly exudates as viscosifier in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…12, 13, and 14 have equal heights, showing the same apparent viscosity for all. This is consistent with earlier works by [39].This is because of the stable repulsive charge polyelectrolyte of the polymer when salinity increases. For the GA, at no salt, the apparent viscosity was higher than for NaCl 0.75%, NaCl 3.5% and CaCl 2 2.0%.…”
Section: Terminalia Mantaly Concentration and Presence Of Ionssupporting
confidence: 93%
See 1 more Smart Citation
“…12, 13, and 14 have equal heights, showing the same apparent viscosity for all. This is consistent with earlier works by [39].This is because of the stable repulsive charge polyelectrolyte of the polymer when salinity increases. For the GA, at no salt, the apparent viscosity was higher than for NaCl 0.75%, NaCl 3.5% and CaCl 2 2.0%.…”
Section: Terminalia Mantaly Concentration and Presence Of Ionssupporting
confidence: 93%
“…The study showed that Terminalia Mantaly polymer has good alkaline at pH above 7 and stable rheological properties as both salinity and temperature are increased. This is as a result of the stable repulsive charges polyelectrolyte of the polymer when salinity increases [39].…”
Section: Terminalia Mantaly (Tm)mentioning
confidence: 99%
“…This means CMC from empty oil palm fruit bunches is a suitable replacement for the industrial counterpart, to sustain cutting in the borehole, without falling or settling at the bottom. A study by Inemugha et al (2019) reported an increase in gel strength with the increase in the content of CMC from Terminalia Mantaly Exudate and consequent prevention of loss circulation.…”
Section: Gel Strenghtmentioning
confidence: 99%
“…Terminaliamantaly exudates have been widely used in the pharmaceutical industry as binding agent in tablet formulation (Oluyemisi et al, 2012;Michael et al, 2017). Its suitability as a viscosifier in water-based drilling mud have also been studied (Inemugha et al 2019). Studies have shown that the molecular structure of this exudates contain highly branched polysaccharides consisting of galacturonic, glucuronic and 4-O-methylglucuronic acids, as well as galactose, arabinose, rhamnose, mannose and xylose but neutral sugars and total uronic acid content may vary with different type of Terminalia gum.…”
Section: Introductionmentioning
confidence: 99%